PHOTOGRAPHIC COLLECTIVES: in search of a definition for a possible vector of decolonial photography - Cajueiro, Tomas (Brazilian journalism research, 2024)
ABSTRACT – This paper examines contemporary photo collectives as a new form of professional photojournalism within the network society, comparing examples from Brazil and Spain. It identifies key elements distinguishing modern collectives from past ones and explores their role in fostering a decolonial approach to photography. The study highlights how marginalized cultures reclaim agency and become central to new photographic narratives, offering diverse epistemologies that address 21st-century crises. RESUMO – Este artigo examina os coletivos fotográficos contemporâneos como uma nova forma de fotojornalismo profissional na sociedade em rede, comparando exemplos do Brasil e da Espanha. Identifica elementos-chave que distinguem os coletivos contemporâneos dos anteriores e explora seu papel na promoção de uma abordagem decolonial da fotografia. O estudo destaca como culturas marginalizadas recuperam a agência e se tornam centrais em novas narrativas fotográficas, oferecendo epistemologias diversas que abordam crises do século XXI. RESUMEN – Este artículo examina los colectivos fotográficos contemporáneos como una nueva forma de fotoperiodismo profesional en la sociedad en red, comparando ejemplos de Brasil y España. Identifica elementos clave que distinguen los colectivos contemporáneos de los anteriores y explora su papel en la promoción de un enfoque decolonial de la fotografía. El estudio destaca cómo las culturas marginadas recuperan la agencia y se convierten en centrales en nuevas narrativas fotográficas, ofreciendo epistemologías diversas que abordan las crisis del siglo XXI.